PENGARUH BEBERAPA RASIO KEUANGAN TERHADAP KEPUTUSAN HEDGING PADA SEKTOR PERTAMBANGAN DI BURSA EFEK INDONESIA - Anggyantari, Putu Mia; Purbawangsa, Ida Bagus Anom (E-Jurnal Manajemen; Vol 9 No 5 (2020)DO - 10.24843/EJMUNUD.2020.v09.i05.p20, 2020)
Companies that conduct international trade will be affected by unexpected changes in the value of foreign currencies, so companies need to hedge derivative instruments. This study aims to analyze the effect of several financial ratios, such as liquidity, leverage and profitability on hedging decisions on derivative instruments. This study uses secondary data from the company's annual report. The population is a mining company listed on the Indonesia Stock Exchange for 2016-2018. Purposive sampling is used with 33 companies analyzed by logistic regression analysis. Liquidity has significant negative effect on hedging decisions of derivative instruments, leverage has significant positive effect on hedging decisions of derivative instruments, profitability has significant negative effect on hedging decisions of derivative instruments. The accuracy of the prediction data for the probability of hedging derivative instruments in companies is 28% and the remaining 72% is explained by other variables outside the model. Keywords: Liquidity, Leverage, Profitability, and Hedging